2020
DOI: 10.1039/c9ta09584e
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous enhancement of the stable power conversion efficiency in perovskite solar cells

Abstract: This work studies spontaneous enhancement in power conversion efficiency of multi-cation-halide perovskite solar cells which occurs days after device fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 64 publications
4
55
0
Order By: Relevance
“…We relate this enhancement to the spontaneous enhancement phenomenon that has been previously reported for PSCs with various perovskite compositions and structures. [51][52][53][54] As portrayed in our previous work, 55 spontaneous enhancement in the PCE of PSCs is a general phenomenon and possibly occurs due to a reduction in straininduced trap states in the bulk of the perovskite materials, which happens gradually over time due to strain relaxation.…”
Section: Resultsmentioning
confidence: 76%
“…We relate this enhancement to the spontaneous enhancement phenomenon that has been previously reported for PSCs with various perovskite compositions and structures. [51][52][53][54] As portrayed in our previous work, 55 spontaneous enhancement in the PCE of PSCs is a general phenomenon and possibly occurs due to a reduction in straininduced trap states in the bulk of the perovskite materials, which happens gradually over time due to strain relaxation.…”
Section: Resultsmentioning
confidence: 76%
“…It is interesting to note that grain growth has been observed by SEM, 6,19 but not with AFM. 7 Unlike AFM, SEM detects not only morphology, but chemical composition as well. 20 This may indicate that a compositional rather than a morphological transformation takes place.…”
Section: Resultsmentioning
confidence: 99%
“…Defects have been shown to be effectively passivated by additives, 4 light soaking 5 or even by storing under dark and dry conditions. [6][7][8] The latter pathway is of particular interest as there are no additional experimental steps or chemicals required. We have shown that the increase in device performance was accompanied by a spontaneous increase in average perovskite grain size, indicating that ions in the perovskite lm are very mobile, allowing the perovskite to self-heal as the ions move through the lattice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations